The Computer Science of Concurrency: The Early Years. - LAMPORT, LESLIE (Communications of the ACM, 2015)
The article presents a speech by computer scientist Leslie Lamport, a computer scientist and the 2013 recipient of the Association for Computing Machinery's (ACM's) A.M. Turing Award, entitled "The Computer Science of Concurrency: The Early Years". It discusses the history of concurrent algorithms in the 1960s and 1970s. Topics discussed include mutual exclusion, producer-consumer synchronization, and distributed algorithms.